Allelopathic effect of Salix caprea litter on late successional plants at different substrates of post-mining sites - pot experiment studies - Mudrák, Ondřej (Jihočeská univerzita, 2012)
The willow Salix caprea is a common colonizer of post-mining sites including those in the Sokolov coal mining district (Czech Republic) where this study was conducted. In one bioassay and two pot experiments, we investigated the effect of S. caprea litter on three plant species (Arrhenatherum elatius, Plantago lanceolata, and Lotus corniculatus) that commonly grow in late successional stages on these sites.
Allelopathic effect of Salix caprea litter on late successional plants at different substrates of post-mining sites - pot experiment studies
Keywords: Restoration; Succession; Salix caprea; Allelopathy; Litter; Vegetation; Restoration; Succession; Salix caprea; Allelopathy; Litter; Vegetation